✔ 最佳答案
The answer is : C. -2a
It should be : x² + 2a² - b² = 2(x + a)² - (x - b)²
x² + 2a² - b² = 2(x + a)² - (x - b)²
x² + 2a² - b² = 2(x² + 2ax + a²) - (x² - 2bx + b²)
x² + 2a² - b² = 2x² + 4ax + 2a² - x² + 2bx - b²
x² + 2a² - b² = x² + (4a + 2b)x + 2a² - b²
Compare the x terms on the both sides :
4a + 2b = 0
b = -2a
2012-08-14 01:59:30 補充:
If it is x² - 2a² - b² = 2(x + a)² - (x - b)²,
then x² - 2a² - b² = x² + (4a + 2b)x + 2a² - b²
Compare the x terms on the both sides :
4a + 2b = 0
b = -2a ...... The answer is also (c)
2012-08-14 02:01:42 補充:
Futhermore, compare the constant tems on the both sides :
-2a² - b² = 2a² - b²
4a² = 0
a = 0
Since b = -2a
then b = 0
2012-08-14 02:02:41 補充:
.....
So, b = a
(b) is also the answer.
2012-08-17 22:45:33 補充:
If it is x^2 - 2a^2 - b^2, the answers are (b) and (c).
It it is x^2 + 2a^2 - b^2, the answer is (c).